2020
DOI: 10.1590/0001-3765202020180969
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with hydrolyzed yeast and its effect on the performance, intestinal microbiota, and immune response of weaned piglets

Abstract: The objective of this study was to evaluate the effects of autolyzed yeast on performance, cecal microbiota, and leukogram of weaned piglets. A total of 96 piglets of commercial line weaned at 21-day-old were used. The experimental design was a randomized block design with four treatments (diets containing 0.0%, 0.3%, 0.6%, and 0.9% autolyzed yeast), eight replicates, and three animals per pen in order to evaluate daily weight gain, daily feed intake, and feed conversion in periods of 0 to 15, 0 to 26, and 0 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Several previous studies have shown the positive effects of yeast cells and the extracts from S. cerevisiae on the growth performance of weaning pigs [14,15]. This is in line with the improvements of ADG, ADFI, and G:F ratio in early-weaning piglets fed HY-supplemented diet with increasing inclusion levels.…”
Section: Growth Performance and Diarrheal Occurrencesupporting
confidence: 77%
See 1 more Smart Citation
“…Several previous studies have shown the positive effects of yeast cells and the extracts from S. cerevisiae on the growth performance of weaning pigs [14,15]. This is in line with the improvements of ADG, ADFI, and G:F ratio in early-weaning piglets fed HY-supplemented diet with increasing inclusion levels.…”
Section: Growth Performance and Diarrheal Occurrencesupporting
confidence: 77%
“…In this study, we observed reductions in IL1, IL6, and TNFα on day 14, inconsistent with previous finding [28], whereby significant changes in IL1 and IL6 secretion were not observed. The discrepancies in the findings may be attributed to the HY source and their composition, while the included level, experimental challenge, and weaning age of piglets could also be contributing factors [15,28,29].…”
Section: Immunoglobulin and Pro-inflammatory Cytokinesmentioning
confidence: 89%
“…Test product 47.86 -Corn starch 1) 36.42 66.28 Dextrose 2) 9.00 20.00 Cellulose 3) 2.00 5.00 Soybean oil 4) 2.00 4.00 Calcium carbonate 0.99 -Monodicalcium phosphate 5) 0.60 3.00 Vitamin and mineral premix 6) 0.30 0.30 Sodium chloride 0.30 0.40 Vitamin E 7) 0.03 0.02 Magnesium oxide 8) -0.10 Potassium carbonate 9) -0.40 Chromic oxide 0.50 0.50 1) Xingmao, Zhucheng Xingmao Corn Developing Co. Ltd., Weifang, China.…”
Section: Assay Diet N-freementioning
confidence: 99%
“…4) Thai Vegetable Oil Public Company Limited, Thonburi, Bangkok. 5) Chanhen, Guizhou Chanhen Chemical Corporation, Fuquan, China. .…”
Section: Assay Diet N-freementioning
confidence: 99%
See 1 more Smart Citation